2006
DOI: 10.1007/s11136-005-0449-7
|View full text |Cite
|
Sign up to set email alerts
|

The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30): Validation Study of the Thai Version

Abstract: The objective of this study was to assess the psychometric properties of the Thai version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) version 3.0. The questionnaire was completed by 310 cancer patients during their follow-up at 2 teaching hospital oncology clinics. About 70% of participants had advanced stage of cancer and 72% had been receiving chemotherapy. Cronbach's alpha coefficients of the six scales were above 0.7, except for cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 18 publications
6
19
1
4
Order By: Relevance
“…Our results indicate that the reliability analysis for multi-item subscales yielded very similar results to the Western, Iranian, Korean and Japanese studies (Aaronson et al 1993;Kobayashi et al 1998;Montazeri et al 1999;Yun et al 2004). The low Cronbach's alpha-coefficient for cognitive functioning subscale is also found in the original (Aaronson et al 1993) and other studies of different cultures (Kobayashi et al 1998;Montazeri et al 1999;Yun et al 2004;Luo et al 2005;Silpakit et al 2006). Although this sub- scale has poor psychometric properties, it is proposed to include clinically relevant items (Luo et al 2005).…”
Section: Discussionsupporting
confidence: 79%
“…Our results indicate that the reliability analysis for multi-item subscales yielded very similar results to the Western, Iranian, Korean and Japanese studies (Aaronson et al 1993;Kobayashi et al 1998;Montazeri et al 1999;Yun et al 2004). The low Cronbach's alpha-coefficient for cognitive functioning subscale is also found in the original (Aaronson et al 1993) and other studies of different cultures (Kobayashi et al 1998;Montazeri et al 1999;Yun et al 2004;Luo et al 2005;Silpakit et al 2006). Although this sub- scale has poor psychometric properties, it is proposed to include clinically relevant items (Luo et al 2005).…”
Section: Discussionsupporting
confidence: 79%
“…This observation was reported in Mexican patients with gastric cancer (Oñate-Ocaña et al 2009), similar to Taiwanese (Huang et al 2007), Thai (Silpakit et al 2006), English (Sprangers et al 1996) and Greek version of the EORTC-QLQ-C30 (Kontodimopoulos et al 2011). This observation was reported in Mexican patients with gastric cancer (Oñate-Ocaña et al 2009), similar to Taiwanese (Huang et al 2007), Thai (Silpakit et al 2006), English (Sprangers et al 1996) and Greek version of the EORTC-QLQ-C30 (Kontodimopoulos et al 2011).…”
Section: Discussionsupporting
confidence: 72%
“…Other studies showed similar values, ranging from 0.62 to 0.94 [6][7][8]10,23 . For the BR23 module, internal consistencies for functional and symptom scales were 0.78 and 0.83, respectively.…”
Section: Discussionmentioning
confidence: 57%
“…In order to observe whether the questionnaire was capable of discriminating different situations 8 , mean scores of women with lymphedema and without it were compared by using the Mann-Whitney test. It is expected that women with lymphedema have a poorer quality of life in comparison with the ones without it.…”
Section: Methodsmentioning
confidence: 99%